HYBRID NOISE FILTERING ALGORITHM BASED ON NEURO-TYPE 2 FUZZY SYSTEMS - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Medical images are often subjected to noise due to the failure of data acquisition hardware at the source. Thus, making it difficult for the radiologist to perform image analysis and give correct diagnosis of the disease. This research presents a new image denoising algorithm based on the combination of neuro-type 2 fuzzy systems. The method not only preserves the information relevant for diagnostic details but also provides a cost-effective solution for recovery of lost information due to noise.